The Cultivation of Curcuma rosesana (Zingiberaceae) from Thailand in Harbin - Lijun, Wei; Qian, Yang; Chen, Wang; Mingyuan, Liu (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
A wild species of Zingiberaceae is found in the North of Thailand. The extract of its rhizome is used to sterilize and clean the air. In order to identify its classificational status and make good use of it, we planted it in the greenhouse in Harbin, China following the culture method used for ginger. After 15 months cultivation in greenhouse in Harbin, it bloomed in August 2000. It was identified as Curcuma rosesara. The result shows that although Curcuma rosesara is wind in Thailand, it can be cultured in greenhouse in Harbin, the rhizome is bigger after growing in Harbin than in Thailand so in can be cultivated in greenhouse to get more rhizome for medical use. Keywords: Curcuma rosesara culture in greenhouse identification *Corresponding author: E-mail: cast@kmitl.ac.th